Increasing Incidence and Prevalence of Diabetes among the Status Aboriginal Population in Urban and Rural Alberta, 1995–2006 - Johnson, Jeffrey A. (Can J Public Health, 2009)
OBJECTIVE: To compare changes in diagnosed diabetes prevalence and incidence among Status Aboriginal men and women living in urban and rural areas of Alberta. METHODS: We compared trends in diabetes prevalence and incidence from 1995 to 2006 based on diagnostic codes from Alberta Health and Wellness (AHW) administrative records for adults aged 20 years and older. The AHW Registry file was used to determine registered Aboriginal status, as well as rural and urban residence (based on postal code). Multivariable logistic regression was used to compare diabetes rates over time, by sex and location of residence. RESULTS: Age- and sex-adjusted diabetes prevalence increased 35% in rural Status Aboriginals, from 10.9 (10.4–11.5) per 100 in 1995 to 14.7 (14.2–15.2) per 100 in 2006. Rates in urban Status Aboriginals increased 22% in the same time period from 9.4 (8.5–10.3) per 100 in 1995 to 11.5 (10.9–12.1) per 100 in 2006. The increases in prevalence were greater (p<0.001) for men (43% and 40%) compared to women (30% and 12%) in rural and urban settings, respectively. Diabetes incidence increased 45% in Status Aboriginal men, from 7.4 (4.9–10.6) per 1000 in 1995 to 10.7 (8.3–13.5) per 1000 in 2006 in urban locations, compared to a 35% increase among Status Aboriginal men living in rural locations (p=0.628). Among Status Aboriginal women, incidence increased by 25% for those living in urban locations, but did not change for those in rural locations (p=0.109). CONCLUSIONS: Prevalence and incidence of diagnosed diabetes were highest in Status Aboriginal women, but these rates have increased faster in men over the past decade, regardless of their location of residence.